Hukum Penguasaan dan Kepemilikan Tanah - Nur Qamariah; Zulfikar Rangga Utama; Lalu Ammar Fathin (Peneliti.net, 2023)
This study aims to find out digital-based agrarian conflict resolution collaboration through the village. The research was carried out by applying normative and empirical legal research methods using books, articles, papers and facts taken from human behavior. The results of this study can be seen from the discussion that has been presented by the authors, related to collaboration, digital-based agrarian conflict resolution through the village. Community development is present as an alternative effort to resolve agrarian conflicts that can be carried out. The research method in this paper is the empirical normative research method with data collection techniques from literature studies and previous research studies. The results of the study show that agrarian conflicts are the most excessive conflicts in Indonesia, especially in villages. Agrarian conflict is caused by two main problems, namely the problem of land administration and land use. In general, efforts to resolve agrarian conflicts are carried out using litigation and non-litigation approaches. Community-based agrarian conflict resolution through community development can be an alternative effort to agrarian conflict resolution that can be done to create results in the form of win-win solutions for the conflicting parties. Community development as an effort to resolve agrarian conflicts is carried out through four main stages, namely the community organizing stage, the visioning stage, the planning stage and the implementation and evaluation stage.